Liability Analysis of Financial Statements According to ISAK 35: (Case Study: SMK Muhammadiyah 2 Surabaya) - Sinta Dei Apriliana (Journal of World Conference (JWC), 2022)
SMK Muhammadiyah 2 Surabaya is a Vocational High School which was established under the auspices of the Mahammadiyah Karangpilang Branch Manager which has problems of lack of accountability and preparation of financial statements according to ISAK 35. This has not been implemented by SMK Muhammadiyah 2 Surabaya schools which have not adopted ISAK 35 financial statements. This study aims to analyze the preparation and determine the treatment of accountability for financial reports at SMK Muhammadiyah 2 Surabaya. In this study, the method used is a qualitative method and uses a descriptive approach and the data collection technique used is primary data and secondary data collected by means of interviews, documentation, observation, and the technique used is data analysis. The results of this study are that the financial statements of SMK Muhammadiyah 2 Surabaya are not in accordance with the financial statements of ISAK 35 because there is no implementation from schools regarding ISAK 35. Suggestions for SMK Muhammadiyah 2 Surabaya to hold training on ISAK 35 financial reports.